2016
DOI: 10.3897/zookeys.626.9633
|View full text |Cite
|
Sign up to set email alerts
|

Two complete mitochondrial genomes from Praticolella mexicana Perez, 2011 (Polygyridae) and gene order evolution in Helicoidea (Mollusca, Gastropoda)

Abstract: Helicoidea is a diverse group of land snails with a global distribution. While much is known regarding the relationships of helicoid taxa, comparatively little is known about the evolution of the mitochondrial genome in the superfamily. We sequenced two complete mitochondrial genomes from Praticolella mexicana Perez, 2011 representing the first such data from the helicoid family Polygyridae, and used them in an evolutionary analysis of mitogenomic gene order. We found the mitochondrial genome of Praticolella m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…Colours for the families as in Fig. 2: light blue -Hygromiidae; green -Geomitridae; brown -Polygyridae; red -Helicidae; dark blue -Camaenidae two clades i.e., Bradybaeninae and Camaeninae, treated frequently as two separate families (Lin et al 2016;Minton et al 2016a;Harasewych et al 2017). Our results agree with the division of Helicidae and Camaenidae into subfamilies (Bouchet at al.…”
Section: Start Codons Stop Codonssupporting
confidence: 86%
See 3 more Smart Citations
“…Colours for the families as in Fig. 2: light blue -Hygromiidae; green -Geomitridae; brown -Polygyridae; red -Helicidae; dark blue -Camaenidae two clades i.e., Bradybaeninae and Camaeninae, treated frequently as two separate families (Lin et al 2016;Minton et al 2016a;Harasewych et al 2017). Our results agree with the division of Helicidae and Camaenidae into subfamilies (Bouchet at al.…”
Section: Start Codons Stop Codonssupporting
confidence: 86%
“…Previous mitogenome phylogenies of stylommatophoran superfamilies (Groenenberg et al 2017;Harasewych et al 2017;Yang et al 2019;Doğan et al 2020) showed a clade of Helicoidea separate from other superfamilies, although mitogenomes of only 11 stylommatophoran superfamilies (Yang et al 2019) out of 26 listed by Bouchet et al (2017) are represented in GenBank. According to Bouchet et al (2017), Helicoidea includes 17 families but hitherto phylogenetic relationships could be analysed only for three or four of them, namely Helicidae, Camaenidae, Geomitridae, and Polygyridae (González et al 2016;Lin et al 2016;Minton et al 2016a;Harasewych et al 2017;Doğan et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From annotated, previously published sequences (accession numbers NC_001816, NC_021747 and NC_017872), we extracted the individual genes following the annotation in the NCBI RefSeq database. However, previous studies, which used the sequence of Ce.nemoralis in mitogenomic phylogenetic analyses, repeatedly resulted in a spuriously long branch for this species (Knudsen et al 2006, González et al 2016, Minton et al 2016, Groenenberg et al 2017). A closer examination of the mitogenome sequence and translation of its protein coding regions revealed a very low quality of the sequence (see also White et al 2011).…”
Section: Methodsmentioning
confidence: 99%